2010
DOI: 10.1073/pnas.0914843107
|View full text |Cite
|
Sign up to set email alerts
|

Functional delivery of viral miRNAs via exosomes

Abstract: Noncoding regulatory microRNAs (miRNAs) of cellular and viral origin control gene expression by repressing the translation of mRNAs into protein. Interestingly, miRNAs are secreted actively through small vesicles called "exosomes" that protect them from degradation by RNases, suggesting that these miRNAs may function outside the cell in which they were produced. Here we demonstrate that miRNAs secreted by EBV-infected cells are transferred to and act in uninfected recipient cells. Using a quantitative RT-PCR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
1,227
2
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,457 publications
(1,279 citation statements)
references
References 35 publications
24
1,227
2
6
Order By: Relevance
“…Thus, secreted miRNAs can serve as a novel class of signaling molecules in mediating intercellular communication [15]. The novel and important functions of the secreted miRNAs were also reported by many other groups [18][19][20][21]. The identification of circulating miRNAs, mainly delivered by cell-secreted MVs, as stable and active signaling molecules opens a new field of research in intercellular and interorganelle signal transduction.…”
Section: Introductionmentioning
confidence: 72%
“…Thus, secreted miRNAs can serve as a novel class of signaling molecules in mediating intercellular communication [15]. The novel and important functions of the secreted miRNAs were also reported by many other groups [18][19][20][21]. The identification of circulating miRNAs, mainly delivered by cell-secreted MVs, as stable and active signaling molecules opens a new field of research in intercellular and interorganelle signal transduction.…”
Section: Introductionmentioning
confidence: 72%
“…However recent reports have increasingly shown that besides the traditional growth factors and cytokines as important players in the secretome, it now appears that most of the cells, including MSCs, secrete large amounts of micro and nano-vesicles, either constitutively or upon activation signals [24]. Although little is still known on the biogenesis and physiological role of these entities, their potential as mediators of cell interactions has been reported by different authors [25][26][27][28]. Indeed exosome or microvesicles can operate in a multitude of ways since they can be considered as complex vectors that can hold known biological molecules.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Ambivalence was apparent for the transport and uptake categories, with most votes in the middle of the range. These results suggest perceived unmet needs across all topics, but especially in cargo loading and cargo transfer.
10.1080/20013078.2018.1535745-F0002Figure 2.EV topics about which we know the “most” [1] to the “least” [5]. Respondents were required to rank the five topics from most [1] to least knowledge [2].
…”
Section: Resultsmentioning
confidence: 99%
“…Studies of extracellular vesicles (EVs) and RNA were united in the mid- to late-2000s by findings that RNA molecules were incorporated into EVs and thereby transferred from cell to cell [1-5]. Communication via extracellular RNA (exRNA) was soon accepted as a novel set of mechanisms to explain the increasingly appreciated paracrine effects of EVs.…”
Section: Introductionmentioning
confidence: 99%